Avaliação do desempenho de meios filtrantes fibrosos na remoção de partículas nanométricas - Barros, Priscila Martins de (2014)
Fibrous filters are highly efficient in removing micrometric particles, but when is related on the removal of particles in the nanometer range, their performance is still poorly understood. During filtration, as the particles are deposited on the filter medium, the pressure drops as much as the collection efficiency tends to increase. Thus, this study aimed to determine the deposition of particles in fibrous filter media and their performance, when clean, during this deposition. A cellulose fiber filter (HEPA) and a polyester one were used in the removal of nanometric particles of NaCl. The deposition was assessed by the pressure drop curves as a function of the accumulated mass. The filter performance was avaliated by counting the particles before and after the filter medium and the pressure was monitored to obtain the filtration curves. The filtration rate was maintained at 6 cm.s-1 and the concentration of the generated solution at 0.0042 L min-1 in a commercial inhaler was 5 g L-1. The results showed that the deposition of these particles ocurred first in the interior of the filters media and then in the surface of both filters. The HEPA filter showed lower permeability, higher specific strength of the cake filtration and lower point of clogging. The efficiencies for the cleaned filters ranged from 99.8 to 100% for the HEPA filter and from 15 to 100% for the polyester filter, for the range of particles avaliated. The theoretical efficiencies fitted to the experimental data in the filter of heterogeneous fibers. For the filter of homogeneous fibers, the data also did fit satisfactorily. Both filters showed, problably in the transition region between the mechanisms of collection, a randomness of experimental data. During deposition, the efficiency of the filter medium increased with the deposition of particles, reaching 100% of efficiency at the end of filtration.